2021
DOI: 10.1101/2021.08.29.457346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional organization and regulation of thePseudomonas putidaflagellar system

Abstract: A single region of the Pseudomonas putida genome, designated the flagellar cluster, includes 59 genes potentially involved in the biogenesis and function of the flagellar system. Here we combine bioinformatics and in vivo gene expression analyses to clarify the transcriptional organization and regulation of the flagellar genes in the cluster. We have identified eleven flagellar operons and characterized twenty-one primary and internal promoter regions. Our results indicate that synthesis of the flagellar appar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
(180 reference statements)
1
1
0
Order By: Relevance
“…Hence, the FleQ bEBP that interacts with RpoN to drive an open complex formation domain is also involved in the regulation of the K1-T6SS. This transcription factor has previously been described to activate several genes, importantly flagellar genes, and by binding to c-di-GMP, derepresses the expression of biofilm component genes [75,76]. As expected for a bEBP of RpoN, the K1-T6SS was induced in the absence of FleQ with a slightly higher level of transcription than that observed in the rpoN mutant background (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Hence, the FleQ bEBP that interacts with RpoN to drive an open complex formation domain is also involved in the regulation of the K1-T6SS. This transcription factor has previously been described to activate several genes, importantly flagellar genes, and by binding to c-di-GMP, derepresses the expression of biofilm component genes [75,76]. As expected for a bEBP of RpoN, the K1-T6SS was induced in the absence of FleQ with a slightly higher level of transcription than that observed in the rpoN mutant background (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…It is yet unclear if this mode of regulation also applies to other bacteria. Transcriptional studies on different species identified genes that appear to be constitutively transcribed, e.g, the fliHIJ gene cluster in Pseudomonas putida (Leal‐Morales et al, 2022) or flgA and fliEFGHIJ in Vibrio campbellii (Petersen et al, 2021). Also in P. aeruginosa , similar genes and operons as in S. putrefaciens ( fliLMNOPQR‐flhB; fleN‐fliA ) are only slightly regulated at the transcriptional level (Dasgupta et al, 2003), suggesting that the proteins may be permanently present.…”
Section: Discussionmentioning
confidence: 99%